Addressing Noncommunicable Disease in Dominican Republic: Barriers to Hypertension and Diabetes Care - Bryan Castro; Louise Ing; Yeri Park; Jasmine Abrams; Mark Ryan (Ubiquity Press, 2018)
Introduction: Noncommunicable diseases (NCDs) significantly contribute to morbidity and mortality worldwide. During medical brigades in Santo Domingo, the Dominican Aid Society of Virginia (DASV) collects data to help understand the dynamics of NCD management. This study presents findings regarding resources and barriers to NCD treatment. Methods: A cross-sectional survey study was conducted in two communities (Los Mina and Paraiso) during the 2014 DASV summer brigade. Descriptive statistics, associations, correlations as well as qualitative analyses were conducted to better understand resources and barriers to care in relation to health care coverage. Results: More than one third (n = 64) of 165 individuals had hypertension and/or diabetes. Thirty-seven percent (Paraiso) and 46% (Los Mina) of study participants did not have health insurance in the previous year. For those that did have insurance, 77% (P) and 89% (LM) visited a physician in the previous year. In this same group, 65% of individuals from Paraiso reported that their health insurance never covered the cost of medications while only a quarter of individuals from Los Mina indicated this. Health insurance and access to physicians and medication varied depending on the community of residence. Surveys indicated that access to affordable medications was an important issue for participants. Also, even though individuals in Los Mina were less likely to have health insurance than those in Paraiso, they were more likely to visit a physician. Conclusion: This study contributes to a greater understanding of health care coverage and access for low-resource communities in the Dominican Republic. Health care access, insurance, and cost sharing differed between these communities, but barriers to care were common. Future investigations could focus on qualitative differences in communities' health insurance coverages and development of interventions to address obstacles to care.